Impact of Working Capital Management on Profitability of Bottler’s Nepal (Terai) - Shrestha, Sanjay (Academic Voices: A Multidisciplinary Journal, 2018)
Manufacturing sector contributes immensely to growth of the economy of any nation. It keeps significant role for socio-economy development. But this manufacturing sector has to face dilemma of manufacturing an appropriate trade-off between working capital and profitability in Nepal. In this study, an attempt has been made to identify the impact of WC management on profitability of Bottlers Nepal Limited. Data analysis has been done using descriptive statistics, Pearson correlation, regression analysis and F-test. The data used to analyze one (1) samples size, out of 3 which has found to be covering period 2010-2017 of Bottlers Nepal Limited(Terai). The working capital represents the independent variable variables are Cash conversion period(CCP), Inventor Conversion period (ICP), Receivable conversion period (RCP)and dependent variables is Return on Assets (ROA).The results revealed that the impact of all four independent variables is tested together on dependent variable (ROA). From the model summary the value of R-square=0.754. It indicates that the five independent variables can explain approximately 75.4% of the proportion of variance of dependent variable. However, it is still left 24.6 % unexplained by these independent variables in this study. This indicates that there is a significant relationship between profitability and RCP and ICP. It is indicate that there is no significant relationship between profitability and CCP and PDP.